Single-Dose Nirsevimab for Prevention of RSV in Preterm Infants - Griffin, M. Pamela; Yuan, Yuan; Takas, Therese; Domachowske, Joseph B; Madhi, Shabir A; Manzoni, Paolo; Simões, Eric A.F; Esser, Mark T; Khan, Anis A; Dubovsky, Filip; Villafana, Tonya; DeVincenzo, John P (The New England journal of medicine, 2020)
Nirsevimab, a monoclonal antibody with an extended half-life, is designed to protect infants from respiratory syncytial virus disease after a single intramuscular dose. This placebo-controlled trial involving 1447 preterm infants at 164 sites in 23 countries assessed the effectiveness of nirsevimab over 150 days after the dose was administered.